Revitalisasi Fungsi Dewan Perwakilan Rakyat Daerah dalam Mengawasi Implementasi Kebijakan Pemerintah di Kota Kupang - Bram Fredric Arison Lubalu; Saryono Yohanes; Dhesy A. Kase (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
This study examines the supervisory function of the Regional House of Representatives (DPRD) of Kupang City in overseeing the implementation of regional government policies from the perspective of constitutional and regional governance law. The research aims to analyze the implementation of the DPRD’s supervisory function, identify factors that hinder its effectiveness, and formulate a revitalization model to strengthen legislative oversight. This study employed an empirical juridical approach using qualitative methods. Primary data were obtained through interviews and field observations, while secondary data were collected from legislation, books, and scientific literature. The findings reveal that the supervisory function of the Kupang City DPRD has been implemented through working meetings, public hearings, discussions of the Regional Head Accountability Report (LKPJ), field visits, and budget oversight. However, supervision remains predominantly administrative and procedural, limiting its contribution to substantive policy improvement. The principal obstacles include weaknesses in legal substance, institutional capacity, and legal culture, which collectively reduce the effectiveness of legislative oversight. To address these issues, this study proposes a revitalization model encompassing institutional capacity building, strengthening supervisory authority, improving human resources, enhancing legal frameworks, reinforcing institutional support, and promoting accountability-oriented legal culture. These efforts are expected to improve the effectiveness of legislative oversight and support transparent, accountable, and democratic regional governance.